Conflict Management Strategies for Early Childhood Educators: An Empirical Perspective - Gilang P, M. Harviend; Syakur, Abd.; Solikhah, Nur Amalia (Journal Corner of Education, Linguistics, and Literature, 2024)
Conflict management is an important skill that needs to be introduced from an early age to support children's social-emotional development. Early childhood is in a critical stage of character formation and interpersonal skills, so mastering conflict management can help them understand emotions, empathize and solve problems constructively. The family environment and formal education play a central role in forming this ability through support, guidance, and strengthening values ​​such as tolerance, cooperation, and communication. This research uses a literature study method to explore the importance of introducing conflict management for young children, as well as effective methods for teaching it. The findings show that methods such as role-play, simple conflict-based stories, and visual media are effective approaches in helping children understand and practice conflict management. This strategy not only supports children's social skills but also forms emotional control and strong moral values. The implications of this research include theoretical contributions in the form of a scientific basis regarding the importance of introducing conflict management, as well as practical benefits in the form of guidance for educators and parents in accompanying children. The research conclusion confirms that the introduction of conflict management from an early age contributes significantly to the formation of children's character who is empathetic, independent, and able to face interpersonal challenges in the future. Therefore, collaboration between families, educators and the child's social environment is the key to success in instilling these skills.